Leptin favors imbalance of antigen-specific CD4+ T-cells associated with severity of cat allergy - Vollmer, Carolina; Dias, Aleida; Sales, Marisa; Sacramento, Priscila M.; Silva, Júlio Cesar; Oyamada, Hugo A. A.; Linhares, Ulisses C.; Gupta, Sudhir; Kasahara, Taissa M.; Bento, Cleonice A. M. (Frontiers in Immunology, 2023)
Introduction: Obesity can complicate IgE-mediated allergic diseases. In the present study, we aimed to investigate the ability of obesity-related concentrations of leptin to modulate the in vitro effector and regulatory Fel d1specific CD4 + T-cell subsets in patients allergic to cat, considered the third most common cause of respiratory allergy in humans.Methods: For this study, plasma and peripheral blood mononuclear cells (PBMC) from 30 cat-allergic patients with mild, moderate and severe respiratory symptoms were obtained. The PBMC cultures were stimulated with Fel d1 antigen (10 µg/mL) in the presence or absence of obesity-related leptin dose (50 g/mL). After 6 days, the levels of cytokines and IgE in the supernatants were evaluated by multiplex and ELISA, respectively. The frequency of different nonfollicular (CXCR5 -) and follicular (CXCR5 + ) Fel d1-specific CD4 + T cell subsets was determined by flow cytometry. The plasma levels of leptin and IgE anti-cat titers were evaluated by ELISA and ImmunoCAP, respectively.Fel d1 induced both IgE production and release of cytokines related to Th2, Th9 and Th17 cell phenotypes. Feld1 was more efficient in increasing the frequency of TFHIL-21 -cells positive for IL-4, IL-5 and IL-13 than TFHIL-21 + cell subsets. Leptin favored the expansion Th2-like and Th9-like cells and TFHIL-21 -cells positive for IL-4, IL-5 and IL-13, but reduced the proportion of conventional (Treg/Tr-1) and follicular (TFR) regulatory CD4 + T-cell subsets expressing or not CD39 marker. Finally, many of the imbalances between Fel d1specific CD4 + T-cells were also correlated with plasma leptin and anti-Fel d1 IgE titers. In summary, hyperleptinemia should negatively impact on the severity of cat allergies by favoring the expansion of pathogenic Fel d1-specific CD4 + T-cell phenotypes and damaging the functional status of regulatory CD4 + T-cell subsets.